Magnetic resonance imaging radiomics in prostate cancer radiology: what is currently known? - Pavel B. Gelezhe; Ivan A. Blokhin; Serafim S. Semenov; Damiano Caruso (Digital Diagnostics, 2022)
Diagnostic and treatment approaches in prostate cancer rely on a combination of magnetic resonance imaging and histological data.